An engineering methodology for constraint corrections of elastic–plastic fracture toughness – Part II: Effects of specimen geometry and plastic strain on cleavage fracture predictions. (September 2015) - Ruggieri, Claudio; Savioli, Rafael G.; Dodds, Robert H.
Highlights: Introduction and application of a modified Weibull stress incorporating plastic strain effects. Fracture toughness values for an A515 Gr 65 steel depend strongly on specimen geometry. Marked differences in crack front stresses between PCVN and large SE(B) specimens. Toughness predictions depend strongly on the adopted plastic strain model. The modified Weibull stress model provides very good toughness predictions. Abstract: This work extends a micromechanics model for cleavage fracture incorporating effects of plastic strain to determine the reference temperature, T 0, for an A515 Gr 65 pressure vessel steel based on a modified Weibull stress ( σ ̃ w ) . Non-linear finite element analyses for 3-D models of plane-sided SE(B) and PCVN specimens define the relationship between σ ̃ w and J from which the variation of fracture toughness across different crack configurations is predicted. The modified Weibull stress methodology yields estimates of T 0 from small fracture specimens which are in good agreement with the corresponding estimates derived from testing of larger crack configurations.